OTHR-41. Amplification of the PLAG family genes – PLAGL1 and PLAGL2 – is a key feature of a novel embryonal CNS tumor type. (3rd June 2022) - Keck, Michaela-Kristina; Sill, Martin; Wittmann, Andrea; Kumar, Piyush Joshi; Stichel, Damian; Sievers, Philipp; Wefers, Annika K; Roncaroli, Federico; Hayden, James; McCabe, Martin G; Kranendonk, Mariëtte E G; Zapotocky, Michal; et al.
Abstract: Pediatric central nervous system (CNS) tumors differ substantially from their adult counterparts, are marked by considerable molecular and clinical heterogeneity, and diagnosis through histopathology alone can be challenging. Using DNA methylation-based CNS tumor classification in combination with copy number and RNAseq analysis, we identify a rare, novel pediatric CNS tumor type (n=32) which is characterized by focal high-level amplification and consecutive overexpression of one of the PLAG family genes – PLAGL1 or PLAGL2. It is epigenetically divergent from other known tumor types such as high-grade gliomas, medulloblastomas, embryonal tumors, or CNS sarcomas. The wide range of original histopathologic diagnosis rendered attests to their polyphenotypic nature in terms of morphology. We suggest that these tumors may arise from early to intermediate neural progenitor cells with some neuronal commitment. Using ChIPseq data, we show that both PLAGL1 and PLAGL2 act as transcription factors for: i) the oncogenic kinase RET, a potential drug target, that was overexpressed in our cohort; ii) components of the Wnt/β-Catenin pathway; iii) a set of imprinted genes, reported to regulate the imprinted gene network in mouse models, that was deregulated in the PLAGL-amplified tumors. Consequently, a 250-gene expression PLAGL-signature indicated dysregulation of imprinting control and differentiation/development as a prominent feature. We report differences regarding age and sex distribution between PLAGL1- and PLAGL2-amplified tumors and shed light on differences in clinical behavior and outcomes between these subtypes in male and female patients. PLAGL1-amplified tumors were more prevalent in school-age children and teenagers, while PLAGL2-amplified cases occurred in very young patients. Kaplan-Meier analysis showed a trend towards a more favorable outcome in patients with PLAGL1-amplified tumors and in female patients. Survival rates remained constant after 5 years with a five-/ten-year overall survival of 75% for PLAGL1, 24% for PLAGL2, 18% for male patients, and 88% for female patients.